Why Did God Make Me This Way? Religious Coping and Framing in the Virtuous Pedophile Community - Cranney, Stephen (Journal for the scientific study of religion, 2017)
"Virtuous Pedophiles" (or VPs) have a sexual attraction to children but view child/adult sexual relations as wrong. Research on VPs is nascent but has theoretical importance for our understanding of sexuality, labeling, and extreme stigma. Their relevance is particularly acute in regard to religious coping and framing. As their primary stressor is a predisposition towards a highly stigmatized (or "sinful") activity, religious VPs find themselves in a unique situation, and it is unknown to what extent they employ conventional religious coping mechanisms. I investigate how VPs use their religious frameworks to make sense of and react to their pedophilia with a survey of respondents recruited from an online VP forum, a content analysis of forum discussions, and several in-depth, semistructured interviews. Religious VPs tend to employ the same basic religious coping mechanisms (both positive and negative) but customize their approaches to accommodate their unique situation. Positive and negative religious coping show the same relationships with mental health as found in other populations. Religiosity is associated with both lower mental distress as well as less cognitive distortions associated with sexual offending.